„Wybór twarzy” − spotkanie Federica Felliniego i Diane Arbus w świetle semantycznych wizji ludzkich fizjonomii - Ziemlewska, Katarzyna (Załącznik Kulturoznawczy, 2022)
This research focuses on two famous artists born in the 20s of the 20th century who have been rarely brought together in comparison. It’s quite astonishing, as – putting aside the discrepancy of their respective biographies – the landscapes made of human faces in their oeuvre have much in common both aesthetically and semantically. As Fellini said in one of his interviews, “I look for my movies in all of the faces that are surrounding me”. The eponymous “selection of faces” was the most important part of the movie castings for the director from Rimini. He was eager to behold all of his upcoming films “in the appearing faces”. Proceeding from face semiology, the etymology of an Ancient Greek πρόσωπον meaning concurrently a “person” and a “mask”, and the problem of mimesis, this paper attempts to analyze the affinity of human physiognomies seen in the movies of Frederico Fellini and in the photographic portraits taken by Diane Arbus. The key to understanding their relatedness seems to be an explicit objection against “democracy of faces”, a withdrawal from staging the human visage to make it more expressive and unconstrained, and the conviction that “a face is not in the camera,” but it resides in the creator’s mind initially.